DIVERSITY OF FEED PLANTS OF SUMATRAN ELEPHANT HABITATS (ELEPHAS MAXIMUS SUMATRANUS) IN JANTHO PINUS NATURE RESERVE, ACEH BESAR DISTRICT - Ma’rifatin Zahrah (Jurnal Natural, 2016)
This research conducted to identify the kinds of feed plants sumatran elephant which is the main component of elephant habitats .The purpose of this research was to obtain data about kinds of feed plants sumatran elephant and analyzes the species diversity. The study conducted with analysis vegetation use of systematic sampling methods at any community different vegetation .The research results recorded there are 75 species of  feed plants  from 269 species of plants found , which means 28%  plants in the study locations is a source of feed for sumatran elephants. The data was obtained show that the number of species to spread of  feed plants of elephant more on a community of  I , a number of 36 species of all level vegetation began to the seedling, sapling, pole and tree; while community II and III each 30 and 23 species . Community IV and V had the same number of  feed plants species, a number of 31 species . Based on the analysis of the diversity of species to feed plants  of elephant, shows that community III have index the diversity of species ( H = 4,53; Hmax = 5,17 ) higher than other locations.